English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-14 12:51:59 · 1 answers · asked by Jerry P 6 in Science & Mathematics Mathematics

1 answers

cos(2x) = cos(x+x)

by the formula for cosine of sum of two angles, which you probably have already learned,

cos(x+x) = cos(x)cos(x) - sin(x)sin(x) = cos^2(x) - sin^2(x)

also, because cos^2(x) + sin^2(x) = 1 by the pythagorean identity, cos(2x) = 1-sin^2(x) - sin^2(x) = 1-2sin^2(x)
by similar reasonining, cos(2x) = 2cos^2(x) - 1

so cos(2x) = cos^2(x) -sin^2(x) = 2cos^2(x) - 1 = 1 - 2sin^2(x)

2006-12-14 13:02:41 · answer #1 · answered by need help! 3 · 0 0

fedest.com, questions and answers